Anesthetic Management in Cerebellopontine Angle Tumor Craniotomy with a History of Nasopharyngeal Tumor - Fitryono, Eko Prasetyo; Prihatno, Muhammad Mukhlis Rudi; Suryani, Shila (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2024)
Background: Cerebellopontine angle (CPA) tumor is the most common type of neoplasm found in the posterior fossa. In this case report, we aim to describe the anesthetic management of craniotomy surgery in patient CPA tumor with a history of nasopharyngeal tumor.Case: A 49 years old female patient, weight 58 kg, was admitted with the main complaint of headache, dizziness, her lips drooped to the right and her left eye could not close completely. The left extremity is weak, walk unsteadily, the vision in both eyes is blurry, the left hearing is decreased. There is a history of nasopharyngeal carcinoma from biopsy results in 2019. The patient is diagnosed with a CPA tumor, a craniotomy will be performed under general anesthesia, the patient is fasted for 8 hours before surgery, which was administration of premedication ondansetron 4 mg iv, dexamethasone 5 mg iv. Preemptive analgesia sufentanyl 15 mcg iv, thiopental induction 250 mg iv, muscle relaxant rocuronium 30 mg iv, fresh gas flow (FGF) 3 L/min, maintenance with sevoflurane gas 2%, rocuronium 20 mg/hour syringe pump, dexmedetomidine 20 mcg/hour syringe pump. Analgetics after surgery patient was given morphin 1 mg/hour syringe pump, paracetamol 3x1 gr iv. After craniotomy the patient condition improved, complaints before surgery decreased.Discussion: In this cases report, patient with CPA tumor underwent craniotomy surgery under general anesthesia. During operation, in neuroanesthesia management is to maintained hemodynamic stability.Conclusion: Anesthetic management of CPA tumor starts from pre-surgical evaluation, premedication, induction, durante position, anesthetic management and supervision. Anesthesia has a very important role in the overall management of these patients to obtain good surgical results.